2019
DOI: 10.17109/azh.65.1.75.2019
|View full text |Cite
|
Sign up to set email alerts
|

Ecological aspects of Red Squirrel (Sciurus vulgaris) dreys in city parks

Abstract: Modified habitats often pose challenges to native fauna. Red squirrels (Sciurus vulgaris) successfully inhabits territory of the cities. However research on quite abundant red squirrel populations in urban parks of Lithuania was lacking. The investigation was carried out in two city parks (area of Giruliai park 152 ha, Pasakų park forest-31 ha) in Vilnius, Lithuania. Both areas were mainly coniferous, dominated with pine (Pinus sylvestris). Drey (N = 415) counts were done in February and March 2014-2016. Dreys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…peanuts) can also cause nutritional deficiencies, which may have health implications in highly urbanised environments where squirrels may not be able to compensate for such malnutrition if there is limited availability of natural food sources (Thomas et al 2018). Finally, feeders may facilitate the spread of parasites and diseases, such as SQPV, by encouraging interactions both between red squirrels and with grey squirrels (Chantrey et al 2014, Kopij 2014, Stirkė 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…peanuts) can also cause nutritional deficiencies, which may have health implications in highly urbanised environments where squirrels may not be able to compensate for such malnutrition if there is limited availability of natural food sources (Thomas et al 2018). Finally, feeders may facilitate the spread of parasites and diseases, such as SQPV, by encouraging interactions both between red squirrels and with grey squirrels (Chantrey et al 2014, Kopij 2014, Stirkė 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Vieira et al (2015) reported that two red squirrel populations, which had been reintroduced into urban parks, were suffering from long‐term declines due to the poor‐quality habitat. Tree species composition in urban greenspaces is also important for providing suitable nesting sites (Kopij 2009, Stirkė 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the studies of Eurasian red squirrel have shown that the concentration of several individuals on feeding tables can have negative effects such as inter-individual conflict (Wauters et al 2002), increased predation risk (Shuttleworth 2001), and the spread of disease (Chantrey et al 2014). Consequently, supplemental feeding can decrease breeding success (Kopij 2009; Stirkeė 2019). In fact, we observed predators such as martens and owls via automatic cameras installed on the feeders during the survey and found collars that had previously been attached to squirrels on the ground near the feeders.…”
Section: Discussionmentioning
confidence: 99%